Health Education for Sustainable E-Waste Management - Ernawati, Kholis; Burhan, Aslichan; Syawqi Albar, Akmal; Al-Khaliel, Achnaf Thoriq; Fawwaz Al-Fatich, Ahda Sabiela (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2024)
A combination of ever-increasing device usage and lightning-fast technological advancements has led to a critical problem: electronic waste. One technique to encourage people to dispose of their electronic waste in a more sustainable fashion is to raise their level of green literacy. Using a literature review approach, this study examines green literacy programs as they pertain to e-waste management. After that, it evaluates the programs' effectiveness and makes recommendations for further developments. This publication uses a thorough literature review technique as its research method. The scholarly sources used were journals, academic books, research reports, and policy documents. The selection of sources was based on their relevance, credibility, and contribution to understanding key themes related to green literacy, public health education, and behavior change in e-waste management practices. Additionally, the analysis focused on the intersection between educational interventions, awareness campaigns and global health initiatives, especially those targeting vulnerable populations such as children and pregnant women. The findings demonstrate that while green literacy can raise public knowledge and comprehension of the significance of responsible e-waste management, there are still obstacles to its widespread adoption. By using social media, communities, and educational institutions, green literacy has the potential to raise awareness about the risks of e-waste and the significance of recycling. However, challenges such as public apathy and limited access to recycling facilities continue to impede the implementation of green literacy. The community, along with the governmental and private sectors, must work together to address these issues and encourage the sustainable disposal of electronic trash. Ongoing education and awareness efforts utilizing many communication platforms, including social media, the media, and educational programs in communities and schools, are necessary to improve e-waste management. In order to create easily accessible recycling facilities and launch programs that reach different societal levels, the government must collaborate with the commercial sector and non-governmental organizations.